EVALUASI KINERJA GURU SEBAGAI UPAYA PENINGKATAN PROFESIONALISME DALAM PROFESI KEPENDIDIKAN - Elvi Mailani; Nurhalimah Siahaan; Cinta Monalisa Kinanti Purba; Claudia Cintia Bella Siahaan; Dini Siva Aulya; Fathia Yasmina Fitri Daulay; Zenatul Khoiriah (STKIP Subang, 2026)
Teacher performance evaluation is a strategic effort to improve teacher professionalism in the education profession. Teachers play a crucial role in shaping the quality of national education, necessitating an evaluation system capable of objectively and sustainably assessing teacher competence and performance. This article aims to analyze the role of teacher performance evaluation in improving teacher professionalism and its impact on the quality of education in Indonesia. The method used is a literature study with a qualitative descriptive approach that examines scientific journals, research articles, and policy documents related to teacher performance evaluation and professional development. The results of the study indicate that systematic and planned teacher performance evaluation can encourage improvements in teachers' pedagogical, professional, social, and personality competencies through academic supervision, training, workshops, learning reflection, and ongoing development. Furthermore, performance evaluation has been shown to play a role in improving the quality of the learning process, building teacher work motivation, and strengthening teachers' abilities to face the challenges of modern education, including environmental literacy and the use of digital technology. Thus, teacher performance evaluation is an important instrument in realizing professional, competitive teachers who contribute to the quality of education in Indonesia.